A case report of early detection of rare femoral shaft bone metastasis in a penis cancer patient - Kumar Yadav Ajay; Kumar Mandal Sandip; Gnawali Suman; Dutta Adhikari Ganga; Sharma Nitu; Shailesh Kumar Pandey; Deepika Dhakal; Pandit Anil (Сибирский онкологический журнал)
Background. Bone metastasis is very common in the advanced stage of numerous carcinomas. In penile carcinoma, lymph nodes metastasis is somehow common but it is very rare reported to be secondary from penile cancer. till the date, there are only few cases of penis carcinoma reported bone metastasis in literature worldwide.Case Presentation. Herein, We presented a 51-year-old Nepalese male with squamous cell carcinoma of penis. computed tomography (ct) scan of the patient revealed that there was carcinoma involving glans penis and precure with bilateral external & internal inguinal lymphadenopathies. After then, the patient was under gone for partial penectomy and bilateral inguinal lymphadenectomy and complete 6-cycle chemotherapy. After one year of treatment, patient developed thigh pain and headache and he advised to have magnetic Resonance imaging (mRi) of brain, 99mTc-MDP whole body bone scan and ct scan of pelvis and thigh. The examination report reveals that there was a sclerotic change in vertex of skull bone and moderate 99mTc-MDP uptake in right proximal shaft of femur just below the neck d/d metastasis. The histopathological examination of the true cut biopsy taken from the lesion of the femur showed metastatic keratinizing squamous cell carcinoma which is rare case of femoral shaft bone metastasis secondary from penile carcinoma. Then patient was sent for surgical reconstruction of femur. Based on the case studies review femur shaft bone metastasis from penile cancer is extremely rare.Conclusion. The best of our knowledge; this is the first early detected bone metastases to shaft of the femur in a patient with penile cancer. early diagnosis helps to radical treatment as well as palliative treatment. surgery is the preferred option of the treatments, especially for metastatic foci in the long bones.